Werkzeuge und Konzepte für die Untersuchung und Entwicklung zukünftiger Kfz-Bremssysteme - Riese, Christian (Karlsruher Schriftenreihe Fahrzeugsystemtechnik, 2022)
The electrification of the power train as well as the automatisation of driving have a strong influence on chassis for future vehicles. Due to the possibility for recuperation using the electric motor a strong shift in the so far used load spectrum can be seen. Furthermore, this increases the high amount of requirements for brake systems. For understanding the interactions and for developing corresponding optimal systems for future vehicles, proper tools and concepts are necessary.